In Situ Quantitative Tensile Testing of Antigorite in a Transmission Electron Microscope - Idrissi, Hosni (J Geophys Res Solid Earth, 2020)
The determination of the mechanical properties of serpentinites is essential toward the understanding of the mechanics of faulting and subduction. Here we present the first in situ tensile tests on antigorite in a transmission electron microscope. A push‐to‐pull deformation device is used to perform quantitative tensile tests, during which force and displacement are measured, while the evolving microstructure is imaged with the microscope. The experiments have been performed at room temperature on 2 × 1 × 0.2 μm(3) beams prepared by focused ion beam. The specimens are not single crystals despite their small sizes. Orientation mapping indicated that several grains were well oriented for plastic slip. However, no dislocation activity has been observed even though the engineering tensile stress went up to 700 MPa. We show also that antigorite does not exhibit a purely elastic‐brittle behavior since, despite the presence of defects, the specimens accumulate permanent deformation and did not fail within the elastic regime. Instead, we observe that strain localizes at grain boundaries. All observations concur to show that under these experimental conditions, grain boundary sliding is the dominant deformation mechanism. This study sheds a new light on the mechanical properties of antigorite and calls for further studies on the structure and properties of grain boundaries in antigorite and more generally in phyllosilicates.